Software engineering for self-adaptive systems. International Seminar, Dagstuhl Castle, Germany, December 15-19, 2013, Revised selected and invited papers /: International Seminar, Dagstuhl Castle, Germany, December 15-19, 2013, Revised selected and invited papers. Assurances : III, (2017) - Unknown
No abstract available